Experimental Research on Environment Assistant Fatigue of Domestic SA-508-Ⅲ-1 Steel and Prediction Model Development for PWR Nuclear Power Plant - SHEN Rui, LIU Chang, TANG Lichen, WANG Bingxi (Yuanzineng kexue jishu, 2025)
The US Nuclear Regulatory Commission issued regulatory guideline RG 1.207 in 2007 and upgraded it in 2018, which not only requires the design of new nuclear power plants to consider the impact of coolant environment on the fatigue life of nuclear level 1 components, but also requires in-service nuclear power plants to consider environment assistant fatigue (EAF) issues when updating their operating licenses. Over the past 30 years, the Argonne National Laboratory (ANL) in the United States and countries such as Japan have obtained fatigue test results in high temperature and high pressure water environments for primary circuits through extensive simulations. EAF models for primary equipment and pipeline materials in nuclear power plants have been established, and technical support documents NUREG/CR-6909 for RG 1.207 guidelines have been released. Due to the fact that the ANL model is based on experimental data from countries such as the United States and Japan, the EAF test data for domestic SA-508-Ⅲ-1 steel is limited, and the test data has not yet been included in the ANL model. Therefore, it is necessary to simulate the fatigue performance of domestic nuclear materials in a primary water environment, verify the applicability of the ANL model to domestic low-alloy steel materials, and develop an environmental fatigue model for domestic materials, provide a design basis for fatigue design, safety review, and life assessment of primary equipment in third-generation nuclear power plants in China. The fatigue properties of domestic SA-508-Ⅲ-1 steel used in primary loop equipments of PWR nuclear power plant at room temperature, 320 ℃ air environment and simulated PWR primary loop water environment were studied, the best fitting curve (average curve) of fatigue properties of domestic SA-508-Ⅲ-1 steel was obtained. Based on this, the effects of strain rate , temperature (T) and dissolved oxygen (DO) on the fatigue properties of domestic SA-508-Ⅲ-1 steel in the primary water environment of PWR nuclear power plant were studied, based on the functional equations of the influencing parameters, the Fen prediction model of the EAF correction factor of domestic SA-508-Ⅲ-1 steel was established. At the same time, comparing to the predicted life of ANL model, the fatigue life of domestic SA-508-Ⅲ-1 steel in the water environment of PWR primary loop is within the limit of 95% confidence limit ( ), which shows that the ANL model can be used to predict the fatigue life of domestic SA-508-Ⅲ-1 steel. Comparing with ANL model, the fatigue prediction model of environmental assistant fatigue obtained by this paper is more suitable for fatigue life prediction of domestic SA-508-Ⅲ-1 steel, which can be used as a reference for the design of the primary loop equipment considering environmental assistant fatigue effect for the third generation nuclear power plant.